(untitled) (Education in the 21st Century, 2024)
The article is devoted to the peculiarities of the teaching nanostructured gas sensors in universities and the problems existing here. The professional literature on this topic was studied, the necessity of using gas sensors in various systems was presented, and the need for courses on gas sensors in the modern universities was justified. The main subsections of the course, the most important provisions included in them, and their teaching methods are presented. Teaching a course on nanostructured gas sensors in universities requires the use of modern methods, including both the experimental and the theoretical knowledge. It is necessary to teach the subject using experimental works with modern measuring and technological equipment. For the good assimilation and the easy knowledge transfer of courses on the nanostructured gas sensors, students need prior knowledge of semiconductor physics, materials science, chemistry, and other related fields.